Training of teaching assistants and teachers of core medical specialties in Paraguay, and influence on practices, years 2017-2018 - Godoy Torales, Gladys Maribel; Samudio, Margarita (Medicina Clínica y Social, 2024)
Introduction: The quality of teaching in medicine depends in part on the level of training of teachers. Objective: Describe the training and its influence on research practice and the use of computing in teaching, of teaching assistants and teachers of the core medical specialties of the National Hospital of Paraguay in the period 2017-2018. Methodolgy: Observational, descriptive-analytical, cross-sectional study, which included teachers and teaching assistants (heads of ward and on-call) of the core medical specialties (medical clinic, pediatrics and gynecology/obstetrics). A questionnaire consisted of closed questions on demographic characteristics, training in university didactics, research and computer science, and experience in teaching and research was used. Sufficient training in research was defined as having a course lasting one year or more; and in computer science according to self-qualification. Descriptive statistic and the chi square test at a significance level of 0.05 were used to determine association between training and research practice, publications, as well as the use of computing in teaching. Results: 64 teachers and assistant teachers participated, 31 (48.4%) from pediatrics, 18 (28.1%) from gynecology-obstetrics and 15 (23.4%) from medical clinic; 7 (10.9%) were teachers, 37 (57.8%) with >10 years of teaching. Sixty-two (96.8%) had training in computer science, 56 (87.5%) in research, and 50 (78.1%) in didactics. 73.4% of the population had sufficient training in didactics, 28.1% in research, and 66.6% in computing. Those with sufficient research training carried out significantly more research (p=0.03) and scientific publication (0.01); and those who had sufficient computer training used it more frequently as a teaching tool, ?= 0.02. Conclusions: In general, teachers need to improve their training, especially in scientific research; since it influences on their performance.
Keywords: Postgraduate Education; professional training; professional competence